Molecular investigation of genetic and environmental factors contributing to obesity in adolescent learners residing in the semi-urban/rural areas of the Western Cape Province, South Africa - Yako, Yandiswa Yolanda (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2012.